1999
DOI: 10.1046/j.1440-1819.1999.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the circadian sleep propensity rhythm and hormonal rhythms under ultra‐short sleep–wake cycle

Abstract: The aim of this study was to clarify effects of hormonal and temperature rhythms on circadian fluctuations of sleep propensity. Ten healthy females underwent 24-h sleep deprivation and entered the circadian sleep propensity assessment setting under the ultra-short sleep-wake schedule. During the experiment, sleep propensity rhythm, rectal temperature, and 24-h serum hormone profiles (melatonin, cortisol and thyroid-stimulating hormone) were investigated. The circadian sleep propensity rhythms had two apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…Our results also contrast with studies that reported no effect of sleep deprivation on melatonin secretion (Jimerson et al, 1977; Touitou et al, 1992; von Treuer et al, 1996; Leproult et al, 1997; Goichot et al, 1998; Kudo et al, 1999; Redwine et al, 2000), and studies showing melatonin amplitude, but not phase, changes (Akerstedt et al, 1979; Salin-Pascual et al, 1988; Rao et al, 1996; Shilo et al, 1999; Goh et al, 2001; Cajochen et al, 2003). We cannot explain why the melatonin phase and amplitude results of our current study differ from our previous baseline studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results also contrast with studies that reported no effect of sleep deprivation on melatonin secretion (Jimerson et al, 1977; Touitou et al, 1992; von Treuer et al, 1996; Leproult et al, 1997; Goichot et al, 1998; Kudo et al, 1999; Redwine et al, 2000), and studies showing melatonin amplitude, but not phase, changes (Akerstedt et al, 1979; Salin-Pascual et al, 1988; Rao et al, 1996; Shilo et al, 1999; Goh et al, 2001; Cajochen et al, 2003). We cannot explain why the melatonin phase and amplitude results of our current study differ from our previous baseline studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies of the effects of wake therapy on melatonin amplitude measures showed primarily no effect (Jimerson et al, 1977; Touitou et al, 1992; von Treuer et al, 1996; Leproult et al, 1997; Goichot et al, 1998; Kudo et al, 1999; Redwine et al, 2000), although some observed an increase (Akerstedt et al, 1979; Salin-Pascual et al, 1988; Goh et al, 2001), and some a decrease (Rao et al, 1996; Shilo et al, 1999; Cajochen et al, 2003). These disparate results may be due to different methodologies employed, including the timing and frequency of the melatonin measurements in relation to sleep deprivation, light and activity conditions, the use of plasma versus urinary or salivary measures, the duration and timing of the change in sleep phase or sleep deprivation, and the method used to analyze melatonin amplitude or phase.…”
Section: Introductionmentioning
confidence: 92%
“…Day sleep is light, fragmented, and more likely to be disrupted and hence, insomnia can be severe in night shift workers (5). It is possible that circadian sleep propensity rhythm and hormonal rhythm are under influence of the circadian pacemaker as well as sleep habits (6). Most rhythms are driven by an internal biological clock located in the hypothalamic suprachiasmatic nucleus and can be synchronized by external signals such as light-dark cycles (7).…”
Section: Discussionmentioning
confidence: 99%
“…The ultra-short sleep/wake protocol has been used to establish circadian rhythms in melatonin (Kripke et al, 2005), sleep propensity (Kudo et al, 1999; Lavie et al, 1981), sleep architecture (Carskadon & Dement, 1975; Stampi, 1992), and neuroendocrine function (Weitzman et al, 1974a; Weitzman et al, 1974b), and to examine phase response curves for bright light (Kripke et al, 2007). However, the ultra-short sleep/wake protocol has been sparsely used in assessing circadian patterns of neurobehavioral performance and mood (Lavie et al, 1987).…”
Section: Introductionmentioning
confidence: 99%